URBANISASI DI KOTA BALIKPAPAN: FORMASI SOSIAL KELUARGA PENDATANG MISKIN DI KOTA BALIKPAPAN - Mutmainnah, A. Nurul; Kolopaking, Lala M; Wahyuni, Ekawati Sri (Pekerjaan Sosial, 2015)
Abstract This aims of study to explain urbanization in Balikpapan  and poverty faced by poor migrant families through social processes and social formations that they experienced. The research method used is the method mix or combination of qualitative and quantitative methods. This study also uses primary data through surveys, in-depth interviews, field diaries and secondary data by dokumentation and articles related to the research. Urbanization in Balikpapan is inseparable by entry of poor families from various regions in Indonesia. Ethnic solidarity apparently affected relations of production, in which poor families are bound migrants in ethnic groups and used as cheap labor in production activities. Modes of subsistence and commercial production of social formation forming families of poor immigrants. Lack of capital and the role of market mechanisms in production activities make poor migrant families are in position of the working class with low incomes and experiencing poverty. Keywords: family poor immigrant, social process, social formation, modes of production,  production relationsAbstrak Penelitian ini bertujuan untuk menjelaskan urbanisasi di kota Balikpapan dan kemiskinan yang dihadapi keluarga pendatang miskin melalui proses sosial dan formasi sosial yang mereka alami. Metode penelitian yang digunakan adalah kualitatif dengan data primer  melalui wawancara mendalam dan catatan harian lapangan. Data sekunder yang digunakan adalah dokumentasi dan artikel yang berkaitan dengan penelitian untuk menjelaskan urbanisasi di kota Balikpapan. Urbanisasi di kota Balikpapan tidak terlepas dari masuknya keluarga miskin dari berbagai wilayah di Indonesia yang ingin mencari kerja. Solidaritas dan kerjasama sesama etnis merupakan salah satu bentuk proses sosial yang dialami keluarga pendatang miskin. Moda produksi subsisten dan komersil menjadi pembentuk formasi sosial keluarga pendatang miskin. Kurangnya modal dan peran mekanisme pasar dalam kegiatan produksi membuat keluarga pendatang miskin berada dalam posisi kelas pekerja dengan pendapatan rendah dan mengalami kemiskinan. Kata kunci: keluarga pendatang miskin, proses sosial, formasi sosial, moda produksi